(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The microbiological quality of commercially packed fruit juices sold in South-East Nigeria were assessed. A total of forty (40) juice samples consisting of orange, apple, pineapple, lemon, and guava flavoured varieties were collected. Samples were screened for total viable count, total coliform count, faecal coliform count, total staphylococcal count and total fungal count using standard microbiological methods. The highest total bacteria load of 4.4×105 cfu/ml was observed in sample A (Orange) while the lowest was observed in sample D of Apple variety (1.95×104 cfu/ml). The total coliform count ranged from no count in samples A, B, C and D to 9.8×101 cfu/ml in sample I (Guava juice). In all the samples, there was no faecal coliform found. The staphylococcal count ranged from no count in samples E, F, I and J to 8.4×102 cfu/ml in sample G (lemon juice). The highest total fungal count of 1.6×105 cfu/ml was observed in sample I (Guava) and the lowest count was observed to be 1.2×103 cfu/ml in an apple juice (sample D). The microorganisms isolated from the samples included Staphylococcus aureus, Bacillus species, Enterobacter species, Acetobacter species, Lactobacillus species, Saccharomyces cerevisiae, Aspergillus species, Rhizopus species and Penicillium species. Bacillus species was the most common (70%), followed by S. aureus (60%), Enterobacter spp., Lactobacillus spp. and Saccharomyces cerevisiae had the same rate of 50% respectively, and Acetobacter spp. and Penicillium spp. had the same rate of 40% while the least occurrence was seen in Aspergillus spp. and Rhizopus spp. with the rate of 30% respectively. The result showed that different bacterial and fungal species occurred within the fruits juices. The materials used for the production of the juice, poor sanitation, extraction, raw material contamination, lack of both proper heat sterilization and adequate quality control during processing of fruit juice could be a contributory factor to the presence of these organisms in the fruit juices. Some of the fungal isolates especially Penicillium sp. and Aspergillus sp. could result in the production of mycotoxins, which could lead to health hazards for the consumer and their presence in the fruit juices is of public health significance. Therefore, regular monitoring of the quality of commercially available fruit juices for human consumption is recommended to avoid outbreak of food borne illness resulting from the organisms encountered in this study.